The Impact of Cultural Intelligence on University Students’ Intention to Study Abroad: The Role of Perceived Value - Anh, Khuc The; Dang, Le Thi Thanh; Ngoc, Nhu Vu Bich; Dat, Ngo Thanh; Ngoc Anh, Tran Thi (VNU Journal of Science: Education Research, 2021)
This research aims to examine the relationship among cultural intelligence (CQ), perceived value (PV) and students’ intention to study abroad. By using data gathered in 739 university students, along with statistical analysis, the carrying out results show that there is a positive correlation between CQ and the intention to study abroad through the mediating role of PV. In particular, CQ and PV have positive influence on students’ intention to study abroad and CQ is an antecedent of PV. This study focuses on the influence of specific factors on the intention to study abroad. Meanwhile, this research contributes to the educational field CQ, which is a totally new factor in Vietnam. With a view to helping students in deciding to participate in study abroad programs and improving the quality of education, advice is given to students and related educational organizations.